Design of Science Process Skill Approach-Based Laboratory Work Instruction - Firmansyah, Veri; Silitonga, Friska Septiani; Khoirunnisa, Fitriah; Setiawaty, Sri (International Journal for Educational and Vocational Studies, 2020)
The development of a Science Process Skills Approach-based Laboratory Work Instruction has been conducted on Heat of Reaction topic. The subject of the research is the students of class XI in Senior High School 2 Tanjungpinang. The research aims to determine the feasibility of laboratory work instruction in terms of the validity and practicality categories. In the category of validity, there are five aspects studied including the aspects of content feasibility, grammar, presentation, graphical design, and science process skills. The validation results obtained from three validators was 92.46% (very valid category). In the practicality category was conducted on 40 students. In this category, there are seven aspects studied, namely aspects of observing, classifying, interpreting, determining hypotheses, applying, designing experiments, and communicating. The result shows that a science process skills approach-based laboratory work instruction is categorized in the practical criteria (82.28%).